The Microbiome of the Worldwide Invasive Ascidian Didemnum vexillum - Casso, Maria; Turon, Marta; Marco, Núria; Pascual, Marta; Turon, Xavier (Frontiers in Marine Science, 2020)
All multicellular organisms, including ascidians, host diverse microbial communities that are essential for their evolution. The global invader Didemnum vexillum is a colonial species native to Japan with two main genetic clades, A (the only invasive) and B, which provides a unique opportunity to assess if the microbiome remains stable in the colonization process or shifts according to local environment. We have analysed, using 16S amplicon sequencing, the microbiome of 65 D. vexillum colonies from 13 populations worldwide including the two clades in the native area, plus samples from a congeneric species and seawater from one of the localities. We found 3,525 zero-radius OTUs (ZOTUs) in D. vexillum, belonging to 36 bacterial and 3 archaeal phyla. The microbiome of this species had a markedly different composition from surrounding seawater and from the congeneric species. For the globally invasive clade A, we found 3,154 ZOTUs, and 8 of them were present in all colonies, constituting a core microbiome with high-abundance (69.57% of the total reads) but low diversity (0.25% of the total number of ZOTUs). The variable component was quantitatively much less important but comprised a highly diverse assemblage. In a multiple regression model, global microbiome structure correlated with differences in temperature range across localities, and also with geographic distances, pointing to horizontal acquisition of the symbionts. However, the ascidian may have a strong capacity to select and enrich its microbiome, as we found that the most abundant ZOTUs from tunic samples had low abundance in seawater samples from the same locality. The microbiome structure also correlated with the genetic distances between colonies obtained in a previous genome-wide analysis, suggesting some potential for vertical transmission. In geographically restricted comparisons, temperature and genetic makeup but not geography explained microbiome structure. The combination of a quantitatively dominant core component and a highly diverse variable fraction in the microbiome of D. vexillum can contribute to the success of this global invader in different environments.